The Fabrique: A Pathfinding Algorithm in a Mobile Game Developed Using Construct 3* - Kusumawardhani, Ruby; Prastiningtiyas, Diah Arifah; Alfianti Oktavia, chaulina (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2025)
The rapid growth of the digital game industry, particularly on mobile platforms, has driven the development of algorithms to enhance gameplay quality and player experience. The A* algorithm is a widely used pathfinding method for controlling the movement of non-playable characters (NPCs) in games. This study aims to evaluate the implementation of the A* algorithm in The Fabrique, a mobile game developed using Construct 3, a 2D game development engine. Testing was conducted across various path and obstacle scenarios. The results indicate that the A* algorithm delivers fast computation time and optimal pathfinding for short-distance navigation. In the medium to high obstacle scenarios, the algorithm maintained good performance with only minimal increases in processing time. The implementation of the A* algorithm in The Fabrique proved effective, contributing to a more dynamic and interactive gameplay experience. With an average user satisfaction rate of 81.94%, the algorithm demonstrates not only technical efficiency but also strong user acceptance.